Socrates, or on Human Knowledge Bilingual Edition - Luzzatto, Simone (Studies and Texts in Scepticism, 2019)
Socrates, Or On Human Knowledge is the first sceptical treatise of the early modern period to be written by a Jew. This work, written in the vernacular and signed by the author describing himself as a "Venetian Jew," must be considered a key work for investigating the intensive transfer of knowledge between Jews and Christians and as a mirror of the contemporary philosophical leanings and social and political changes.